Effectiveness of Fibrin Sealant after Cementless Total HIP Replacement: A Double-Blind Randomized Controlled Trial. (January 2013) - Randelli, F.; Banci, L.; Ragone, V.; Pavesi, M.; Randelli, G.
Fibrinogen-based sealants have been used to improve hemostasis after total hip replacement (THR) with conflicting results. We therefore conducted a double-blind randomized controlled trial to determine whether the commercially available fibrin sealant Quixil is effective in reducing the volume of red blood cell transfusions, postoperative blood loss and postoperative hemoglobin drop. Patients with coxarthrosis scheduled for primary cementless THR, were enrolled in a single hospital setting and randomized to either a fibrin sealant group (n=35) or a negative control group (n=35). The surgeon was blind to group allocation until the moment of fibrin application, while the cardiologist determining the need for transfusions remained blind throughout the intervention. In the fibrin sealant group, less blood was lost in the first 48 hours (median, 125 vs 200 ml), fewer patients required allogeneic blood transfusion (1 vs 6 in the control group), and fewer total units of allogeneic blood were transfused (2 vs 12). These differences, however, were not significant partly due to confounding from the use of autologous transfusion of predeposited blood (according to a more liberal regime) and intraoperative autologous blood reinfusion in some patients of both groups. Excluding these last individuals from analysis, no remaining patient of the fibrin sealant group had an allogeneic blood transfusion that, instead, was carried out on 5 patients (23.8%) of the control group (p=0.048). Overall postoperative hemoglobin drop from baseline was significantly less in the fibrin-treated group on day 7 (mean, 3.5 vs 4.5 g/dl; p=0.02). No adverse events were associated with fibrin treatment. These results strengthen the evidence in support of the safety and efficacy of the use of fibrin sealant in improving hemostasis after THR. Clinical trial registration: EudraCT 2008-002024-28.